The correlation between insulin-like growth factor binding protein 1 (IGFBP-1) and homeostasis model assessment of insulin resistance (HOMA-IR) in polycystic ovarian syndrome with insulin resistance - Arini Firmansyah; Maisuri Tadjuddin Chalid; Retno Budiati Farid; Nusratuddin Abdullah (Shahid Sadoughi University of Medical Sciences, 2018)
Background: The underlying etiology of polycystic ovarian syndrome (PCOS) is unknown and assumed to have a strong correlation with insulin resistance. Homeostasis Model Assessment of insulin resistance (HOMA-IR) is a good tool to assess insulin resistance. Low levels of serum Insulin-like Growth Factor-Binding Protein-1 (IGFBP-1) in PCOS women led to the hypothesis that hyperinsulinemia in PCOS inhibits the production of IGFBP-1, which in turn stimulates excessive androgen production. Objective: The study is aimed to analyze the correlation between the levels of IGFBP-1 and HOMA-IR on insulin resistance in PCOS. Materials and Methods: A cross-sectional study among 105 PCOS women, including 60 women with insulin resistance were recruited. The mean of IGFBP-1 and HOMA-IR were 6.507±4.7821 μg/l and 3.633±1.666 respectively. Results: Low levels of IGFBP-1 were detected in all insulin resistance women. There was a correlation between HOMA-IR and overweight (p=0.045), while IGFBP-1 showed no correlation with overweight (p=0.106). In addition, no correlation between IGFBP-1 with HOMA-IR as a marker of insulin resistance was detected. Conclusion: Despite the decrease in IGFBP-1, it seems that there is no correlation between IGFBP-1 with HOMA-IR as a marker of insulin resistance.